Variation of Urate Transport in the Nephrons in Subtypes of Hyperuricemia - Nakamura, Toru (S. Karger AG, 2013)
BACKGROUND: Hyperuricemia cases (HU) can be classified into four subgroups by combining the two main causes of hyperuricemia, i.e. urate underexcretion and overproduction. These subgroups are as follows: underexcretion-type cases (UE); overproduction-type cases (OP); combined-type cases, and normal-type cases. Since urinary urate excretion (Uua) and urate clearance differ significantly between UE and OP, urate transport in the nephrons and the intratubular urate contents might also differ. Such differences might help clarify the pathophysiology of urate underexcretion in subgroups of hyperuricemia, and thus reveal its underlying mechanisms. METHODS: Urate transport coefficients in each subtype of HU were determined employing the previously reported benzbromarone-loading urate clearance tests. The subtype cases of HU were plotted on a graph of urate transport coefficients versus Uua as coordinates. The characteristic features in the distribution of subtype cases on graphs were analyzed in relation to Uua. RESULTS: The mean (±standard error) tubular secretion rate (TSR) in the UE (48.7 ± 1.7 ml/min) was significantly lower and the postsecretory urate reabsorption rate (R(2)) in the UE (0.904 ± 0.004) was significantly higher than those in the normal controls (78.0 ± 2.1 ml/min and 0.877 ± 0.003) or the OP (61.1 ± 3.2 ml/min and 0.861 ± 0.009). Decrements of TSR and increments of R(2) in the UE were largest in the subtypes of the HU, in terms of case numbers and the deviation rate of the group. Conversely, decrements of TSR and increments of R(2) were smallest in the OP. A significant correlation was identified between TSR and Uua (r = 0.345, p < 0.0001), and a significant negative correlation was also found between R(2) and Uua (r = −0.393, p < 0.0001). CONCLUSION: In the UE, hyperuricemia is induced mainly by urate underexcretion, which results from the combination of two main causes in urate transporters of the nephron: significantly lower TSR and significantly higher R(2). Neither of these was observed in OP. Differences in urate transporters in subtypes of the HU might be important not only for understanding the pathophysiology and mechanisms of urate underexcretion and hyperuricemia, but also for providing a strategic therapy for hyperuricemia.